CHARITY IN SECULAR EDUCATION IN THE STAVROPOL PROVINCE IN SECOND HALF XIX - EARLY XX c.c. IN THE CONTEXT OF RUSSIAN MODERNIZATION PROCESS - T. E. Pokotilova (Гуманитарные и юридические исследования)
The article studies the developmet of charitable activity in the system of education in Stavropol province in the second half of the XIX -early XX c.c. as an important factor of Russian modernization changes.